Relationship Between Pemphigus Vulgaris Severity and PCR-positive Herpes Simplex Virus - Sharon Baum; Itai Atar; Dan Coster; Sara Dovrat; Michal Solomon; Eli Sprecher; Tal Zeeli; Aviv Barzilai (Medical Journals Sweden, 2022)
Pemphigus vulgaris is a rare autoimmune skin disease. Although herpes simplex virus has been associated with autoimmune diseases, evidence regarding its association with pemphigus vulgaris exacerbations is scarce. This retrospective cohort study aimed to characterize the epidemiological and clinical features of patients with pemphigus vulgaris who were herpes simplex-positive, compared with those who were herpes simplex-negative, during disease onset. Of 62 patients with pemphigus vulgaris who underwent PCR testing for herpes simplex virus, 25 (40.3%) were positive, with a mean age of 56.1 ± 15.5 years; 35.5% were male. The herpes-positive group had significantly elevated levels of C-reactive protein, Pemphigus Disease Activity Index score, and shorter time to relapse. The time to remission, number of exacerbations per year, and remission status were non-significantly elevated in the herpes-positive group. Thus, routine testing lesions from patients with pemphigus for herpes simplex virus should be performed. If positive, antiviral treatment should be initiated; and preventive antiviral treatment should be considered in severe cases.